The Effect of Trustworthiness, Attractiveness, Expertise, and Popularity of Celebrity Endorsement - Yolanda Mayang Sari; Rina Suthia Hayu; Muhartini Salim (University of Merdeka Malang, 2021)
This study aims to determine the impact of trust, attractiveness, expertise, and popularity (Suhay Salim) celebrity endorsement on the purchasing decisions of Korean skincare brand